Sutan Sjahrir's Character Education Values in Indonesian Historical Records - Ari Yuda Kusuma; Aman Aman (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
A dignified national generation can be formed by instilling the values of character education. Value is a normative standard that influences humans in determining their choices. One of the figures who has the value of character education and has a big influence in Indonesia is Sutan Sjahrir as one of the founding fathers of the Nation. The purpose of writing this paper is to find out the values of character education contained in Sutan Sjahrir as one of Indonesia's heroes based on his existence in Indonesia's historical records. The method used in this writing is library research. Library research or library research is a research method that utilizes library sources to obtain research data. Data analysis includes four components, namely data collection, data reduction, data display, and data verification or conclusion drawing. The basic character values possessed by Sutan Sjahrir include religion, tolerance, democracy, hard work, responsibility, creative, independent, communicative and fond of reading. Sutan Sjahrir's character education values for the nation & state are related to those stated, including patriotism, love for the country, self-sacrifice, nationalism, and social care. These values are very useful in shaping character to create the next generation who has a social spirit and become the pride of the family, nation and state. Tolerance, democracy, hard work, responsibility, creative, independent, communicative and fond of reading. Sutan Sjahrir's character education values for the nation & state are related to those stated, including patriotism, love for the country, self-sacrifice, nationalism, and social care. These values are very useful in shaping character to create the next generation who has a social spirit and become the pride of the family, nation and state. tolerance, democracy, hard work, responsibility, creative, independent, communicative and fond of reading. Sutan Sjahrir's character education values for the nation & state are related to those stated, including patriotism, love for the country, self-sacrifice, nationalism, and social care. These values are very useful in shaping character to create the next generation who has a social spirit and become the pride of the family, nation and state.